Effect of seed layers on dynamic and static magnetic properties of Fe65Co35 thin films. (3rd July 2018) - Akansel, Serkan; Venugopal, Vijayaharan A; Kumar, Ankit; Gupta, Rahul; Brucas, Rimantas; George, Sebastian; Neagu, Alexandra; Tai, Cheuk-Wai; Gubbins, Mark; Andersson, Gabriella; Svedlindh, Peter
Abstract: Fe65 Co35 thin films have been deposited on SiO2 substrates using sputtering technique with different choices of seed layer; Ru, Ni82.5 Fe17.5, Rh, Y and Zr. Best soft magnetic properties were observed with seed layers of Ru, Ni82.5 Fe17.5 and Rh. Adding these seed layers, the coercivity of the Fe65 Co35 films decreased to values of around 1.5 mT, which can be compared to the value of 12.5 mT obtained for films deposited without seed layer. Further investigations were performed on samples with these three seed layers in terms of dynamic magnetic properties, both on as prepared and annealed samples, using constant frequency cavity and broadband ferromagnetic resonance measurements. Damping parameters of around 8.0 10 −3 and 4.5 10 −3 were obtained from in-plane and out-of-plane measurements, respectively, for the as prepared samples, values that were reduced to about 6.5 10 −3 and 4.0 10 −3 for annealed samples.